Marketing analysis of brand Yves Saint Laurent in portfolio L´Oréal - Petránková, Tereza (2012)
The aim of this thesis Marketing analysis of brand Yves Saint Laurent in portfolio L'Oréal is analysis of brand Yves Saint Laurent. The theoretical part focuses mainly on marketing, brand, luxury, analysis of brand and marketing strategies. Practical part based on the findings in theoretical part analysed brand - history, indentity, value and marketing strategy and reccomend new marketing strategies.